ENHANCING HETEROGENEOUS STUDENT'S MOTIVATION IN SPEAKING ENGLISH THROUGH STAD METHOD - Rahman, Izza Amalia; Nurbatra, Laela Hikmah (Premise: Journal of English Education and Applied Linguistics, 2023)
This classroom action research aims to enhance heterogeneous students' motivation to speak English. Heterogeneity in motivation is the difference between cognitive abilities and beliefs, cognitive abilities, and risk preferences, as well as a person's interest in something. A problem found was that one of the best classrooms' students needed more motivation to speak English. It influenced their English lesson score, with the average being 76.6. Therefore, this CAR created a solution to solve this problem by using a method named STAD. The subjects of the research were 34 students of X-D SMAN 3 Malang. In collecting data, the researchers used questionnaires, observation, and tests. Cycle 1 resulted in no significant development of students’ motivation. Their average score was 80.77. By reflecting on the implementation of STAD in cycle 2, students' motivation increased significantly, affecting their score (average: 82.94). This score development happened because students' motivation also increased. Students know how to manage their group collaboration well and better than before to achieve the group’s goals, especially regarding students' cognitive abilities and beliefs. Students believed that with better collaboration, they could develop their cognitive ability by achieving good scores and problem-solving understanding in speaking English